2015
DOI: 10.1155/2015/951768
|View full text |Cite
|
Sign up to set email alerts
|

Hypomagnesemia Induced by Long-Term Treatment with Proton-Pump Inhibitors

Abstract: In 2006, hypomagnesemia was first described as a complication of proton-pump inhibitors. To address this issue, we systematically reviewed the literature. Hypomagnesemia, mostly associated with hypocalcemic hypoparathyroidism and hypokalemia, was reported in 64 individuals on long-term proton-pump inhibitors. Hypomagnesemia recurred following replacement of one proton-pump inhibitor with another but not with a histamine type-2 receptor antagonist. The association between proton-pump inhibitors and magnesium me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 59 publications
2
50
0
1
Order By: Relevance
“…Similarly, Gau et al (14) reported significantly lower serum magnesium levels among hospitalized adults who were using PPIs prior to admission time, thus concluding an association between PPI use and the occurrence of hypomagnesemia, whereas Janett et al (15), in a systematical review of the literature about the association between PPIs and magnesium metabolism, concluded that PPIs may cause hypomagnesemia and thus advised switching to a histamine type 2 receptor antagonist. Findings of these studies are in line with that of a recent prospective study that demonstrated the association between prolonged PPI use and increased risk of hypomagnesemia in the general population, but the authors acknowledge as a limitation the fact that they had a single serum magnesium measurement and were unable to investigate the potential changes of serum magnesium levels after the initiation of PPI therapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Gau et al (14) reported significantly lower serum magnesium levels among hospitalized adults who were using PPIs prior to admission time, thus concluding an association between PPI use and the occurrence of hypomagnesemia, whereas Janett et al (15), in a systematical review of the literature about the association between PPIs and magnesium metabolism, concluded that PPIs may cause hypomagnesemia and thus advised switching to a histamine type 2 receptor antagonist. Findings of these studies are in line with that of a recent prospective study that demonstrated the association between prolonged PPI use and increased risk of hypomagnesemia in the general population, but the authors acknowledge as a limitation the fact that they had a single serum magnesium measurement and were unable to investigate the potential changes of serum magnesium levels after the initiation of PPI therapy (16).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, reduced glomerular filtration rate and De Toni‐Debré‐Fanconi tubulopathy induced by these antimicrobials result from drug accumulation and toxicity within the proximal tubule cells . Finally, proton‐pump inhibitors, which are often prescribed in cystic fibrosis, impair the intestinal magnesium absorption and tend to cause hypomagnesemia …”
Section: Discussionmentioning
confidence: 99%
“…In patients on PPI and medications known to cause hypomagnesemia, baseline magnesium levels should be checked and replaced appropriately with oral or intravenous formulations. H2RA therapy should be considered if magnesium levels continue to stay low while receiving PPI therapy …”
Section: Adverse Effects Of Proton Pump Inhibitorsmentioning
confidence: 99%
“…These findings were confirmed by a larger prospective study of 250 patients which revealed stable magnesium levels after 12 months of PPI use. 40 Janette et al 54 addressed the association between PPI and magnesium metabolism in a systematic review consisting of 14 case-control, cross-sectional studies. An association was found in 11 of them: 6 reports found that the use of PPIs is associated per se with a tendency towards hypomagnesemia; 2 found that this tendency is more pronounced in patients concurrently treated with diuretics; another study showed similar effects with corboplatin and cisplatin use; and 2 studies found a relevant tendency to hypomagnesemia in patients with poor renal function.…”
Section: Long-term Effectsmentioning
confidence: 99%
See 1 more Smart Citation